COGNITIVE FEATURE STAGES OF TASKS IN INTERNATIONAL COMMUNICATION 3 STUDENT’S BOOK BY AMERICAN CORNER UNTAN: A REVISED BLOOM’S TAXONOMY ANALYSIS - Yosephine Fransiska Nawawi; Sudarsono Sudarsono; Dwi Riyanti (STKIP Persada Khatulistiwa Sintang, 2023)
This descriptive and qualitative study aims to assess the relevance of the students' materials to the revised Bloom's taxonomy cognitive domain and the prominent cognition aspect in the lesson book. This study focuses on the English student's book